Marine Propulsion Simulation. Methods and Results - Martelli, Michele (De Gruyter, 2015)
The propulsion system behaviour is a key aspect for the overall dynamics of a ship. However, despite its great importance, numerical methodologies for detailed investigations on marine propulsion dynamics are not yet widely covered in scientific literature. This book presents the main steps for the development of a multi-physic simulation platform, able to represent the motions of a twin screw ship in six degrees of freedom, taking into account the whole propulsion system and automation effects. A number of mathematical sub-models had been developed and calibrated by a set of experimental tests, in model and full scale. Finally, the sea trials campaign of a ship is used to validate and tune the developed simulator. The proposed simulation methodology can be used in the ship preliminary design phase, in order to plan and test the propulsion system and automation. Further applications can include the design optimization and crew training.